Exploitation of the Rohingya Crisis by Jihadist Groups : implications for Bangladesh s Internal Security - Bashar, Iftekharul (S. Rajaratnam School of International Studies)
The exploitation of the ongoing Rohingya crisis by jihadist groups can potentially undermine Bangladesh s hard-earned counter-terrorism achievements. Dhaka can neither ignore the Rohingya crisis nor can it host a large number of refugees on its soil. Therefore, a carefully thought response is needed to deal with this humanitarian crisis. Notwithstanding Bangladesh s humanitarian approach towards Myanmar s Rohingya refugees, it must guard itself against a possible resurgence of militancy.
Keywords: Yihad; Seguridad; Bangladesh; Birmania